Effects of three husbandry systems on health, welfare and productivity of organic pigs. (14th February 2019) - Leeb, C.; Rudolph, G.; Bochicchio, D.; Edwards, S.; Früh, B.; Holinger, M.; Holmes, D.; Illmann, G.; Knop, D.; Prunier, A.; Rousing, T.; Winckler, C.; et al.
Abstract : Organic pig husbandry systems in Europe are diverse – ranging from indoor systems with concrete outside run (IN) to outdoor systems all year round (OUT) and combinations of both on one farm (POUT). As this diversity has rarely been taken into account in research projects on organic pig production, the aim of this study was to assess and compare pig health, welfare and productivity in these three systems. Animal health and welfare were assessed using direct observation and records of 22 animal-based measures, comprising 17 health-, 3 productivity- and 2 behavioural measures. These were collected in pregnant sows, weaners and fattening pigs during direct observations and from records within a cross-sectional study on 74 farms (IN: n = 34, POUT: n = 28, OUT: n = 12) in eight countries. Overall, prevalence of several animal health and welfare issues was low (e.g. median 0% for pigs needing hospitalisation, shoulder lesions, ectoparasites; <5% for runts, tail lesions, conjunctivitis). Exceptions in particular systems were respiratory problems in weaners and fatteners (IN: 60.0%, 66.7%; POUT: 66.7%, 60.0%), weaning diarrhoea (IN: 25.0%), and short tails in fatteners (IN: 6.5%, POUT: 2.3%). Total suckling piglet losses (recorded over a period of 12 months per farm) were high in all three systems (IN: 21.3%; POUT: 21.6; OUT: 19.2%). OUT had lower prevalences of respiratory problems, diarrhoea and lameness of sows. POUT farms in most cases kept sows outdoors and weaners and fatteners similar to IN farms, which was reflected in the results regarding several health and welfare parameters. It can be concluded, that European organic pigs kept in all three types of husbandry system showed a low prevalence of health and welfare problems as assessed by our methodology, but respiratory health and diarrhoea should be improved in weaners and fatteners kept indoors and total piglet mortality in all systems. The results provide benchmarks for organic pig producers and organisations which can be used in strategies to promote health and welfare improvement. Furthermore, in future research, the identified health and welfare issues (e.g. suckling piglet mortality, weaning diarrhoea) should be addressed, specifically considering effects of husbandry systems.